Direct comparison of in vivo versus postmortem second‐order motion‐compensated cardiac diffusion tensor imaging. Issue 4 (22nd August 2017) - Stoeck, Christian T.; von Deuster, Constantin; Fleischmann, Thea; Lipiski, Miriam; Cesarovic, Nikola; Kozerke, Sebastian
Abstract : Purpose: To directly compare in vivo versus postmortem second‐order motion‐compensated spin‐echo diffusion tensor imaging of the porcine heart. Methods: Second‐order motion‐compensated spin‐echo cardiac diffusion tensor imaging was performed during systolic contraction in vivo and repeated upon cardiac arrest by bariumchloride without repositioning of the study animal or replaning of imaging slices. In vivo and postmortem reproducibility was assessed by repeat measurements. Comparison of helix, transverse, and sheet (E2A) angulation as well as mean diffusivity and fractional anisotropy was performed. Results: Intraclass correlation coefficients for repeated measurements (postmortem/in vivo) were 0.95/0.96 for helix, 0.70/0.66 for transverse, and 0.79/0.72 for E2A angulation; 0.83/0.72 for mean diffusivity; and 0.78/0.76 for fractional anisotropy. The corresponding 95% levels of agreement across the left ventricle were: helix 14 to 18°/12 to 15°, transverse 9 to 10°/10 to 11°, E2A 15 to 20°/16 to 18°. The 95% levels of agreement across the left ventricle for the comparison of postmortem versus in vivo were 20 to 22° for helix, 13 to 19° for transverse, and 24 to 31° for E2A angulation. Conclusions: Parameters derived from in vivo second‐order motion‐compensated spin‐echo diffusion tensor imaging agreed well with postmortem imaging, indicating sufficient suppression of motion‐induced signal distortions of in vivo cardiac diffusion tensor imaging. Magn Reson Med 79:2265–2276, 2018. © 2017 International Society for Magnetic Resonance in Medicine.